Sur le vocabulaire de l’haruspicine hittite - Laroche, E.
ersch. 1971; ni = nipašuriš; ši = šintaḫiš = KI.GUB (danânum?); ki = keldiš = šulmum; UZUZÉ = martum; KASKAL-iš = padânum; SUtum, SUti = urnirniš(?) = ubânum(?); NÍG.AŠ; zi = zizaḫiš; uzuTERANU; KÁ.GAL; ŠÀ-ir = ker; SAG.ME.